(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Modern healthcare trends are increasingly shifting toward a biopsychosocial–spiritual approach. Patambaan Siliwangi at Dzikir Al-Fath Islamic Boarding School offers a distinctive model that integrates spiritual practice (dzikir), bioenergy (inner energy), psychological therapy (hypnotherapy), and biochemical treatment (ethnopharmacology). This study aims to analyze the integrative mechanisms and the effectiveness of this model in treating chronic diseases. The research adopts a qualitative medical ethnography method, using a retrospective analysis of 100 medical records from 2025. The findings indicate an average success rate of 88%. The integration of dzikir and hypnotherapy was found to enhance mental resilience, while a precisely dosed formulation of seven herbal ingredients (measured in milligrams) effectively reduced symptoms of cancer and metabolic disorders. The synergy between Islamic spirituality and Sundanese local wisdom has produced a robust prototype of holistic psychotherapy.